2015
DOI: 10.1002/ccr3.208
|View full text |Cite
|
Sign up to set email alerts
|

A case of conjoined twins after a transfer of a multinuclear embryo

Abstract: Key Clinical MessageA pregnancy with conjoined twins was observed after transfer of a multinuclear embryo. As nuclear mechanisms have a role in cellular differentiation, association between multinucleation and fetal malformations is possible. Follow-up studies on children born after transfer of embryos with bi/multinuclear blastomeres are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Embryos that blastomere containing more than one single interphase nucleus on Day-2 or Day-3 are known as MNB [5] .The causative factors may be response to ovarian stimulation and intrafollicular hypoxia disturbing oocyte spindle organization during the oocyte retrieval process [8,9] .MNB may result from insu cient culture medium or from cooling of the oocyte during manipulation leading to alterations of the cytoskeleton [10,11] .Previous studies demonstrated that embryos with MNB had a decreased implantation potential, an increased level of chromosome abnormality [12,13,14,15] and an increased risk of spontaneous abortion [5,8,16,17,12,14,15] .Moreover, multinucleated embryos development slower than non-multinucleated embryos [18] .Nevertheless, still had some MNB embryos were able to achieve pregnancies [19,20] and early multinucleation was not directly related to a lower implantation rate [18,21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Embryos that blastomere containing more than one single interphase nucleus on Day-2 or Day-3 are known as MNB [5] .The causative factors may be response to ovarian stimulation and intrafollicular hypoxia disturbing oocyte spindle organization during the oocyte retrieval process [8,9] .MNB may result from insu cient culture medium or from cooling of the oocyte during manipulation leading to alterations of the cytoskeleton [10,11] .Previous studies demonstrated that embryos with MNB had a decreased implantation potential, an increased level of chromosome abnormality [12,13,14,15] and an increased risk of spontaneous abortion [5,8,16,17,12,14,15] .Moreover, multinucleated embryos development slower than non-multinucleated embryos [18] .Nevertheless, still had some MNB embryos were able to achieve pregnancies [19,20] and early multinucleation was not directly related to a lower implantation rate [18,21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only around 15 cases of post-IVF/ICSI conjoined twins are reported in the literature and no extensive studies are available in this lineage. 4 Conjoined twinning can either be due to ventral or dorsal fusion. Ventral fusion can be lateral, rostral or caudal, and dorsal fusion can be craniopagus, rachipagus or pygopagus.…”
Section: Postnatal Imagingmentioning
confidence: 99%
“…Finnish investigators recently reported the first known case of conjoined twins conceived after transfer of a multinuclear embryo (Mankonen et al, 2015). The mother, 33 years of age and healthy, was referred to the clinic because of her partner's infertility.…”
Section: Embryo Transfer and Conjoined Twinningmentioning
confidence: 99%